ICT in Education in Global Context
XII, 283 p. 59 illus.
Keywords: This book presents the current advances and emerging trends in digital technologies for learning and education through a number of invited chapters on key research areas. It addresses information and communications technology (ICT) in a global context, reporting on emerging trends and issues in four areas – basic education, technical and vocational education, distance and continuing education, and higher education –, as these four areas represent the primary contexts in which ICT is used to support learning and instruction. This book provides a brief overview of the potential benefits of ICT used in education and some of the best approaches in which different ICTs have been used in education thus far in a global context. It also presents the expertise and the most current research and practices of recognized international educators and researchers in the field of ICT in education. Third, this volume is both informative and transformative in its coverage of the conceptual and practical impact of technology on current educational practices, making it a valuable resource for policymakers, educators and educational researchers around the globe.